Modelo de gerenciamento da qualidade da água: estudo do decaimento de cloro na rede de distribuição - Biondo, Flavia Dezan (2019)
The potable water quality is assured by the adequate maintenance of the residual chlorine’s concentration in usage points, this being an important standard to ensure the efficacy of distribution systems of water safe for human consumption. However, reactions between the water volume, the wall of the pipe, degradation reactions of organic matter and other reactive substances, in addition to reactions with the pipe’s rust, result in the decrease of residual chlorine’s concentration. In this context, the aim of this study was to simulate, calibrate and validate a hydraulic model and a water quality model for the free residual chlorine’s concentration in a sector of the municipal water distribution network. The hydraulic model was simulated, calibrated and validated according to operational standards. The quality model was simulated with the aid of a computational tool as well as field and lab parameters. The bottle test was used to find the kinetic coefficients of the free residual chlorine’s decay, kb (chlorine decay in the flow’s volume) and kw (chlorine decay in the pipe’s wall), which were used as basis for the construction of the water quality’s simulation in the system, with the aid of a tool to simulate the hydraulic and quality model. In the quality model, a cost analysis was elaborated with four scenarios: current scenario with concentration of 1,42 mg.L-1, C1 with concentration of 0,65 mg.L-1, C2 with concentration of 0,85 mg. L-1 and C3 with concentration 1,00 mg.L-1. The values of Kb and Kw found were, respectively, 0,013 dia-1 and 0,001 m/dia, and the scenario that obtained the greatest savings was scenario C1, with a lower concentration and consequently a lower cost. The results showed that the chlorine decay in the network is low, meeting Decree MS 2.914/11, where the free residual chlorine is between 0,2 mg.L-1 and 2,0 mg.L-1. Since the public service providers of sanitation must guarantee the water quality and there is no systematic study to define critical points, this study intends to systematize the definition of the maintenance of quality through simulation and analysis of a model of water quality.